Toward Inclusive Digital Mobility Services: a Population Perspective. Issue 4 (2nd July 2022) - Goodman-Deane, Joy; Kluge, Jakob; Roca Bosch, Elisabet; Nesterova, Nina; Bradley, Mike; Waller, Sam; Hoeke, Lisette; Clarkson, P John
Abstract: Digital mobility services have great potential to increase passengers' transportation options, improve their experiences and reduce exclusion. However, these advantages are only available to those who can access and use these services effectively. To facilitate the development of inclusive services, information is needed on the range of potential users' technology access, use, attitudes and capabilities. A population-representative survey examining these characteristics was carried out with 1010 participants in Germany in 2020. The results are examined for groups and intersections of groups identified in previous work as particularly vulnerable to either digital or mobility exclusion. Older people, people with disabilities and people with low education levels had particularly low levels of all technology variables. Caution is thus required when rolling out digital mobility services. Non-digital alternatives are needed to ensure an inclusive service and any digital interfaces need to be designed carefully to be usable by and reassuring to digital novices.